The case of „POSESJA”, European bison cow from Kiermusy (European Bison Conservation Newsletter, 2012)
On 15 August 2011, the European bison’s breeder from Kiermusy reported that one of the lowland bison cows, named Posesja (No 11019) was showing symptoms of a disease in the form of diarrhea. Its feces were loose and reeking. It was recommended to isolate the female from the herd and for the concentrated feed to be withdrawn. Prescribed diet included a combination of hay, oak bark and water ad libitum. By August 18, 2011 there was no improvement to the health status of Posesja. It was decided that vet’s consultation was necessary in order to apply an appropriate treatment. It was decided that Posesja should beimmobilized, in order to implement the detailed examination, collect the material for laboratory tests and administer proper treatment. First, the material for parasitological (feces) and bacteriological (rectal swab) examination was collected from the cow. Blood samples were also collected for biochemical and diagnostic tests against bovine viral diarrhea and paratuberculosis.Generally Shotapen® (Penicillium proc., Penicillium Ben., Streptomycinum) was administered at a dose 1ml/10 kg intramuscularly. In addition to that, an immunostimulatory preparation, Immodulen® (10ml/animal) was used as well as Vetahepar® (12ml/animal which eliminates indigestion and stimulates digestion. The standard formulation of Ivermectin 1%® (1ml/50 kg) was also used as the antiparasitic treatment. Then the cow was monitored for few days and, after the first test, there was a significant improvement. Posesja was not apathetic, eagerly consumed the food. Her stool was semisolid, with the consistency typical for this species. It was recommended to administer medicinal charcoal with water for the following three days. The additional study did not confirm the suspected infection of bovine viral diarrhea virus (BVD-MD). However, it showed relatively low levels of parasitic infections which, seemed not to be a reason for such severe clinical signs. Thus, the final diagnosis was established that it was a case of idiopathic diarrhea, probably caused by dietary errors (improper feed energy balance), and secondary complications caused by pathogenic bacteria. According to the experts in the field of animal feeding, during summer the concentrates should be withdrawn or its amount significantly reduced. Any deficiency of sodium can be supplemented with salt licks. Animal nutrition (both as a dietary therapy and in day-to-day breeding) is just as important as prevention and treatment. Bison breeders should be aware that a higher dose of energy in feed is not necessarily positive for the functioning of the digestive tract and animal body in general. To sum up, natural roughage, diversified with an addition of concentrates, ensure proper physiology of digestive processes and, consequently, make animals healthy and ”happy”.
Keywords: European bison; diarrhea; Kiermusy; treatment; diet